Effect of Anti-Hypertension Counseling Training on Increased Pharmacist Knowledge in Public Health Centers in Pandeglang Regency - Yusransyah . (Journal of Global Pharma Technology, 2016)
Pharmaceutical Care by Pharmacist at Public Health Centers in Pandeglang is not considerably optimal. This can be seen from the increasing of the using anti-hypertensive drugs from year to year at Public Health Center, as the biggest cause of death in Pandeglang Regency categorized to non-communicable diseases. This requires pharmacists to optimize their roles further by increasing their knowledge and capability through training. This study aimed to assess knowledge level and ability of Pharmacists in Public Health Centers in Pandeglang Regency and to find out whether a significant influence could be emerged before and after training. This research was a pre-experimental study with the design of one group given pretest and posttest. Training was held twice. The first training was held in Pandeglang Regency and about Communication Skill and the second one was held in Bandung City and about Anti-Hypertensive Therapy. The results of this study indicated that in the first training the number of respondents who was not good or respondents classified as poor knowledge was 42.86% before training, the number declined after training to 7.14% and the increasing on the number of respondents classified as good enough or fair respondents, from 57.14% before training to 92.86% after training. The average score was 66.57 after training higher than the score before training was 55.36. Moreover, the second training indicated that the number of respondents who classified as poor knowledge before training was 85.71%, the number of declined after training to 14.29% and the increasing on the number of respondents classified as knowledgeable or good respondents, from 0% before training to 14.29% after training. The average score after training was 68.9 higher than the score before training was 42.5. In conclusion, both the first training and the second training can increase Pharmacist knowledge and ability to give Pharmaceutical Care about anti-hypertension.Keywords: Anti-hypertension, Counseling Training, Knowledge Level, Pharmacists.